Generalised Taylor and Generalised Calvo Price and Wage Setting: Micro-evidence with Macro Implications - Dixon, H.; Le Bihan, Herve (Wiley-Blackwell, 2012)
The Generalised Calvo and the Generalised Taylor models of price and wage setting are, unlike the standard Calvo and Taylor counterparts, exactly consistent with the distribution of durations observed in the data. Using price and wage micro-data from a major euro area economy (France), we develop calibrated versions of these models. We assess the consequences for monetary policy transmission by embedding these calibrated models in a standard dynamic stochastic general equilibrium model. The Generalised Taylor model is found to help rationalise the hump-shaped and persistent response of inflation, without resorting to the counterfactual assumption of systematic wage and price indexation. © 2012 The Author(s). The Economic Journal © 2012 Royal Economic Society.